The Effect of Plant-Based Diet on Stress Scores in Inpatients - Ahmad Yani; Shifa Dwi Anggraeni; Suci Amalia (Universitas Negeri Semarang, 2024)
Background: Stress is the physical and mental reaction of a person trying to adapt to internal and external pressures. One of the external pressures is the provision of diet in the hospital. A plant-based diet (PBD) is a general term for a plant-based diet that primarily includes plant-based foods. This study aims to determine the effect of PBD administration on stress scores in inpatients at Purwakarta Holistic General Hospital (RSUHP). Methods: This type of research is experimental with a quasi-experimental study approach and one group pre and post-design research. A total of 19 subjects met the inclusion and exclusion criteria. Fill out the questionnaire for the initial stress condition of treatment (pre), the administration of dietary intervention by the hospital, and the questionnaire for the stress condition at the end of treatment (post). Stress score data was taken using the DASS-Stress questionnaire, and data analysis was done using the Wilcoxon test. Results: The effect of PBD administration on stress score was shown (p=0.001), with an average stress score of 11.84 at the beginning and 4.15 at the end of treatment. Conclusion: There was an effect of PBD administration on stress scores in inpatients at RSUHP.